2019
DOI: 10.1017/s0142716419000328
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of studies on metaphor comprehension in individuals with autism spectrum disorder: Do task properties matter?

Abstract: Individuals with autism spectrum disorder (ASD) often experience difficulty in comprehending metaphors compared to individuals with typical development (TD). However, there is a large variation in the results across studies, possibly related to the properties of the metaphor tasks. This preregistered systematic review and meta-analysis (a) explored the properties of the metaphor tasks used in ASD research, and (b) investigated the group difference between individuals with ASD and TD on metaphor comprehension, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 109 publications
(274 reference statements)
4
41
0
Order By: Relevance
“…Another argument explaining the poorer metaphorical comprehension in ASD is related to the task properties. A recent meta-analysis (Kalandadze et al, 2019) noted that individuals with ASD may demonstrate more difficulties in tasks requiring integration of multiple modalities (although this observation was based on the results of only two studies). In particular, while tasks requiring verbal explanations appeared to be the most demanding task for participants with ASD, decisions about meaningfulness appeared to be the easiest.…”
Section: Introductionmentioning
confidence: 99%
“…Another argument explaining the poorer metaphorical comprehension in ASD is related to the task properties. A recent meta-analysis (Kalandadze et al, 2019) noted that individuals with ASD may demonstrate more difficulties in tasks requiring integration of multiple modalities (although this observation was based on the results of only two studies). In particular, while tasks requiring verbal explanations appeared to be the most demanding task for participants with ASD, decisions about meaningfulness appeared to be the easiest.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several researchers have shown that people with autism have difficulties with metaphor comprehension [ 15 , 16 , 17 ]. Metaphor is “but one of many techniques, named and unnamed, for likening one thing to another by means of words” [ 18 ].…”
Section: The Linguistic Framework In Imagination and Metaphor Theomentioning
confidence: 99%
“…Because there was no Norwegian validated or standardized metaphor comprehension task, we created a multiple-choice task to assess metaphor comprehension. This multiple-choice format reduced the potential confounding impact of verbal communication demands such as metalinguistic and expressive language skills (Kalandadze et al, 2019 for a comprehensive review of metaphor task properties; Pouscoulous, 2011). The task included 24 metaphorical items and 24 literal items.…”
Section: Examining Metaphor Comprehensionmentioning
confidence: 99%